Modified nano silicon dioxide, offshore wind power high-strength grouting material prepared using the modified nano silicon dioxide, and preparation method
Through the combination of modified nanosilicon dioxide and other additives, the problems of low strength and poor durability of offshore wind grouting materials are solved, and high strength, good fluidity and strong durability of offshore wind grouting materials are achieved.
Patent Information
- Application Number
- CN202310562840.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-18
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-05-18
AI Technical Summary
When faced with seawater erosion and strong wind loads, existing offshore wind grouting materials have low strength and poor durability, making it difficult to meet the high requirements of offshore wind farms.
Modified nanosilicon dioxide is used to promote micelle formation and coat nanosilicon dioxide by adding anionic surfactant and chloride salt to the nanosilicon dioxide, thereby improving its dispersion, avoiding agglomeration, and combining carbon nanometers. Tubes, steel fibers and vinyl acetate-ethylene copolymer emulsions were prepared to produce high-strength and high-flow offshore wind grouting materials.
It significantly improves the compactness and compressive strength of the grouting material, enhances its resistance to seawater erosion, and ensures high flowability and good durability of the grouting material.
Smart Images

Figure BDA0004235659170000061 
Figure BDA0004235659170000071 
Figure BDA0004235659170000072
Abstract
Description
Technical Field
[0001] The invention belongs to the field of grouting materials, and in particular relates to modified nano silicon dioxide, and a high-strength offshore wind power grouting material prepared by using the modified nano silicon dioxide and a preparation method thereof. Background Art
[0002] During the construction of offshore wind farms, in order to withstand strong wind loads, seawater corrosion, wave impact, etc., the construction of offshore wind turbine foundation structures is far more complicated than onshore ones, with high technical difficulty and cost as much as 15-25% of the total cost. The particularity of offshore wind power grouting is that the material is required to have high flow viscosity and high stability in the pumping liquid phase, and at the same time, the material is required to have ultra-high strength and ultra-high durability after hardening. A few foreign companies such as Denmark's Densit, Germany's BASF and Singapore's NAUTIC have offshore wind power grouting products and technologies, and have a large number of engineering cases in Europe. The compressive strength of imported products used for wind power grouting can reach 130-160MPa. Compared with the stringent technical requirements of wind power grouting, most of the current domestic grouting has problems such as low strength, poor resistance to marine environment, and poor durability.
[0003] Nanomaterials can improve the strength, wear resistance, chloride ion permeability, frost resistance and microstructure of concrete materials, and have a significant reinforcing effect, such as nano silicon dioxide. However, due to its small size, large specific surface area and high surface energy, nanomaterials absorb water seriously during the mixing process of concrete materials, are not easy to disperse evenly, and are prone to agglomeration, which greatly affects the fluidity of concrete materials, and cannot give full play to the characteristics of nanomaterials, limiting its application in concrete materials and even grouting materials. Based on this, those skilled in the art have modified nanomaterials to improve their agglomeration properties, but most of the existing improvements are to form a thin film on the surface of nanomaterials and graft organic matter. For example, nanomaterials are connected to organic substrates to form nanomaterials with surface organic coatings, which prevent the occurrence of agglomeration and improve their dispersibility. Summary of the invention
[0004] Purpose of the invention: The technical problem to be solved by the present invention is to provide a new type of modified nano-silica, a high-strength offshore wind power grouting material prepared by the modified nano-silica and a preparation method. The modified nano-silica has good dispersibility and does not agglomerate, which improves the density and strength of the grouting material, and can effectively prevent the invasion of chloride ions, effectively solving the problem of offshore wind power grouting material being eroded by seawater.
[0005] Technical solution: The modified nano-silica of the present invention comprises the following raw materials by weight: 4-8 parts of nano-silica, 2-4 parts of anionic surfactant and 2-3 parts of chloride salt; wherein the anionic surfactant is sodium dodecyl sulfate, sodium dodecyl alcohol polyoxyethylene ether sulfate or dodecyl phosphatide triethanolamine, and the chloride salt is calcium chloride, aluminum chloride or sodium chloride.
[0006] The modified nano silicon dioxide comprises the following steps: dissolving an anionic surfactant in water, adding a chloride salt and dissolving it, then adding nano silicon dioxide, stirring and reacting at 50-65° C. for 10-20 minutes, then ball milling at a rotation speed of 200-350 r / min for 20-40 minutes, and finally washing, centrifuging, and low-temperature drying to obtain the modified nano silicon dioxide.
[0007] When modifying nano-silicon dioxide, the present invention adds chloride salt based on the addition of anionic surfactant. The addition of chloride salt can promote the significant growth of anionic surfactant micelles in the anionic surfactant, and the dissociation degree of micelles in the ionic environment is relatively low, which increases the number of anionic surfactant micelles coating nano-silicon dioxide, thereby preventing the agglomeration of nano-silicon dioxide, and achieving the improvement of the dispersibility of nano-silicon dioxide without grafting an organic matrix, avoiding the agglomeration of nano-silicon dioxide; and the release of free water in the silica agglomerates and the reduction of cohesion and friction between particles, thereby improving the fluidity of the grouting material. At the same time, the addition of chloride salt can promote the formation of CASH gel and Friedel salt in the gelling system. Since the gelling system contains aluminum oxide, part of the CSH gel is polymerized into Al-containing 3+ CASH gel, nano-silica and Friedel salt have a filling effect, which can fill the pores inside the grouting material, making the internal structure dense, and can also effectively prevent the invasion of chloride ions, effectively solving the problem of offshore wind power grouting materials being eroded by seawater.
[0008] The offshore wind power high-strength grouting material of the present invention comprises the following raw materials by weight: 35-45 parts of special cement, 35-45 parts of fine aggregate, 5-20 parts of mineral admixture, 10-15 parts of calcium sulfoaluminate expansion agent, 3-5 parts of steel fiber, 1-2 parts of admixture, 0.5-1 part of the above-mentioned modified nano silicon dioxide, 2-5 parts of vinyl acetate-ethylene copolymer emulsion and 0.2-0.5 part of carbon nanotube dispersion.
[0009] The grouting material of the present invention improves the fluidity of the grouting material and the elastic modulus of the grouting material by adding modified nano silicon dioxide and combining the vinyl acetate-ethylene copolymer emulsion and the carbon nanotube dispersion, thereby enhancing the performance of resisting the impact of seawater.
[0010] Furthermore, the special cement used in the grouting material of the present invention can be a mixture of ordinary Portland cement and sulphoaluminate cement in a weight ratio of 1:(0.1-0.2).
[0011] Furthermore, the fine aggregate used in the grouting material of the present invention is a mixture of 10-30 mesh quartz sand and 30-55 mesh quartz sand in a weight ratio of 1:(0.8-1).
[0012] Furthermore, the mineral admixture used in the grouting material of the present invention is a mixture of fly ash and mineral powder in a weight ratio of 1:(4-5).
[0013] Furthermore, the admixtures used in the grouting material of the present invention are polycarboxylic acid water reducer, defoamer and plastic expansion agent in a weight ratio of 1: (0.1-0.2): (0.05-0.1), wherein the defoamer is an organosilicon powder defoamer and the plastic expansion agent is azodicarbonamide.
[0014] Furthermore, the carbon nanotube dispersion used in the grouting material of the present invention is prepared by the following steps: dissolving a polyoxyethylene polyoxypropylene ether dispersant in water, adding carbon nanotubes and stirring until they are dissolved, and then ultrasonically dispersing for 30-40 minutes to obtain the carbon nanotube dispersion; wherein the mass ratio of carbon nanotubes to dispersant is 1:(0.5-1).
[0015] The method for preparing the above-mentioned offshore wind power high-strength grouting material of the present invention comprises the following steps:
[0016] (1) mixing special cement, fine aggregate, mineral admixture and calcium sulphoaluminate expansion agent to prepare powder A;
[0017] (2) mixing and stirring the modified nano-silicon dioxide and the additive to obtain powder B;
[0018] (3) Powder A and powder B are mixed and stirred, and then added into carbon nanotube dispersion and vinyl acetate-ethylene copolymer emulsion, and the water-cement ratio is adjusted to 0.16-0.17 to prepare offshore wind power grouting material.
[0019] Beneficial effects: Compared with the prior art, the significant advantages of the present invention are: the grouting material is based on special cement, fine aggregate, mineral admixture, calcium sulfoaluminate expansion agent and admixture, and adopts modified nano-silica, which significantly improves the density and compressive strength of the grouting material without affecting the fluidity; and at the same time combines carbon nanotubes, steel fibers, vinyl acetate-ethylene copolymer emulsion and carbon nanotube dispersion, so that the prepared grouting material has the advantages of high fluidity, high strength, high elastic modulus, good durability, etc., and can be used in the construction of offshore wind turbines. DETAILED DESCRIPTION
[0020] The technical solution of the present invention is further described in detail below in conjunction with embodiments.
[0021] It should be noted that, except for the modified nano-silica and carbon nanotube dispersion, the raw materials used in the present invention can be purchased from the market, and the raw materials used in the preparation of the modified nano-silica and carbon nanotube dispersion can also be purchased from the market.
[0022] The special cement used in the grouting material of the present invention is a mixture of ordinary silicate cement and sulphoaluminate cement in a weight ratio of 1: (0.1-0.2). The fine aggregate is a mixture of 10-30 mesh quartz sand and 30-55 mesh quartz sand in a weight ratio of 1: (0.8-1). The mineral admixture is an ultrafine mineral admixture, which is a mixture of ultrafine fly ash and ultrafine mineral powder in a weight ratio of 1: (4-5). The admixture is a polycarboxylic acid water reducer, a defoamer and a plastic expansion agent in a weight ratio of 1: (0.1-0.2): (0.05-0.1), wherein the defoamer is an organosilicon powder defoamer and the plastic expansion agent is azodicarbonamide. The carbon nanotube is a multi-walled carbon nanotube with a diameter of 10-20nm or 20-40nm.
[0023] Example 1
[0024] The raw materials used for the modified nano-silicon dioxide in this embodiment are shown in Table 1 below.
[0025] Table 1 Modified silica raw material components of Example 1
[0026] Serial number raw material Content / portion 1 Nano Silica 4 2 Sodium Lauryl Sulfate 2 3 Sodium chloride 2
[0027] The raw materials used in the grouting material of this embodiment are shown in Table 2 below.
[0028] Table 2 Grouting material raw material components of Example 1
[0029] Serial number raw material Content / portion 1 Special cement 35 2 fine aggregate 35 3 Ultrafine mineral admixture 20 4 Calcium sulphoaluminate expansion agent 10 5 Steel Fiber 3 6 Admixtures 1 7 Modified Nano Silica 0.5 8 Vinyl acetate-ethylene copolymer emulsion 2 9 Carbon Nanotube Dispersion 0.2
[0030] The preparation method of the grouting material of this embodiment comprises the following steps:
[0031] (1) Preparation of modified nano-silica: Sodium dodecyl sulfate was completely dissolved in 50 ml of water, sodium chloride was added, and nano-silica was added after the sodium chloride was completely dissolved, and the mixture was stirred at 50° C. for 10 min, and then poured into a ball mill, and reacted for 30 min using a planetary ball mill at a speed of 200 r / min, and then taken out, washed, centrifuged, and low-temperature dried to obtain modified nano-silica;
[0032] (2) Preparation of carbon nanotube dispersion: Dissolve polyoxyethylene polyoxypropylene ether dispersant in water, add carbon nanotubes (the ratio of the two is 1:0.5), stir on a magnetic stirrer for 5 minutes, and after the two are dissolved, place the dispersion in an ultrasonic disperser and ultrasonically disperse for 30 minutes to obtain a carbon nanotube dispersion.
[0033] (3) Special cement, fine aggregate, ultrafine mineral admixture and calcium sulfoaluminate expansion agent are mixed and stirred to obtain powder A; modified nano-silicon dioxide and admixtures are mixed and stirred to obtain powder B; powder A and powder B are mixed and stirred, carbon nanotube dispersion and vinyl acetate-ethylene copolymer emulsion are added, and the water-cement ratio is adjusted to 0.17 to obtain high-strength and high-modulus offshore wind power grouting material.
[0034] Example 2
[0035] The raw materials used for the modified nano-silicon dioxide in this embodiment are shown in Table 3 below.
[0036] Table 3 Modified silica raw material components of Example 2
[0037] Serial number raw material Content / portion 1 Nano Silica 6 2 Sodium dodecyl alcohol polyoxyethylene ether sulfate 2 3 Calcium chloride 2
[0038] The raw materials used in the grouting material of this embodiment are shown in Table 4 below.
[0039] Table 4 Grouting material raw material components of Example 2
[0040] Serial number raw material Content / portion 1 Special cement 36 2 fine aggregate 31 3 Ultrafine mineral admixture 19 4 Calcium sulphoaluminate expansion agent 14 5 Steel Fiber 3 6 Admixtures 1 7 Modified Nano Silica 0.5 8 Vinyl acetate-ethylene copolymer emulsion 2 9 Carbon Nanotube Dispersion 0.3
[0041] The preparation method of the grouting material of this embodiment comprises the following steps:
[0042] (1) Preparation of modified nano-silica: Sodium dodecyl sulfate was completely dissolved in 50 ml of water, and aluminum chloride was added. When the aluminum chloride was completely dissolved, nano-silica was added, and the mixture was stirred at 50° C. for 20 min. The mixture was then poured into a ball mill, and reacted at a speed of 250 r / min for 20 min. The mixture was taken out and washed, centrifuged, and dried at low temperature to obtain modified nano-silica.
[0043] (2) Preparation of carbon nanotube dispersion: Dissolve the polyoxyethylene polyoxypropylene ether dispersant in water, add carbon nanotubes (the ratio of the two is 1:0.6), stir on a magnetic stirrer for 6 minutes, and after the two are dissolved, place the dispersion in an ultrasonic disperser and ultrasonically disperse for 30 minutes to obtain a carbon nanotube dispersion.
[0044] (3) Special cement, fine aggregate, ultrafine mineral admixture and calcium sulfoaluminate expansion agent are mixed and stirred to obtain powder A; modified nano-silicon dioxide and admixtures are mixed and stirred to obtain powder B; powder A and powder B are mixed and stirred, carbon nanotube dispersion and vinyl acetate-ethylene copolymer emulsion are added, and the water-cement ratio is adjusted to 0.162 to obtain high-strength and high-modulus offshore wind power grouting material.
[0045] Example 3
[0046] The raw materials used for the modified nano-silicon dioxide in this embodiment are shown in Table 5 below.
[0047] Table 5 Modified silica raw material components of Example 3
[0048] Serial number raw material Content / portion 1 Nano Silica 8 2 Dodecyl phosphite triethanolamine 2 3 Aluminum Chloride 2.5
[0049] The raw materials used in the grouting material of this embodiment are shown in Table 6 below.
[0050] Table 6 Grouting material raw material components of Example 3
[0051]
[0052]
[0053] The preparation method of the grouting material of this embodiment comprises the following steps:
[0054] (1) Preparation of modified nano-silica: Sodium dodecyl sulfate was completely dissolved in 50 ml of water, and calcium chloride was added. When the calcium chloride was completely dissolved, nano-silica was added, and the mixture was stirred at 55° C. for 15 min. The mixture was then poured into a ball mill, and reacted for 30 min using a planetary ball mill at a speed of 250 r / min. The mixture was then taken out, washed, centrifuged, and dried at low temperature to obtain modified nano-silica.
[0055] (2) Preparation of carbon nanotube dispersion: Dissolve polyoxyethylene polyoxypropylene ether dispersant in water, add carbon nanotubes (the ratio of the two is 1:0.7), stir on a magnetic stirrer for 7 minutes, and after the two are dissolved, place the dispersion in an ultrasonic disperser and ultrasonically disperse for 35 minutes to obtain a carbon nanotube dispersion.
[0056] (3) Special cement, fine aggregate, ultrafine mineral admixture and calcium sulfoaluminate expansion agent are mixed and stirred to obtain powder A; modified nano-silicon dioxide and admixtures are mixed and stirred to obtain powder B; powder A and powder B are mixed and stirred, carbon nanotube dispersion and vinyl acetate-ethylene copolymer emulsion are added, and the water-cement ratio is adjusted to 0.164 to obtain high-strength and high-modulus offshore wind power grouting material.
[0057] Example 4
[0058] The raw materials used for the modified nano-silicon dioxide in this embodiment are shown in Table 7 below.
[0059] Table 7 Modified silica raw material components of Example 4
[0060] Serial number raw material Content / portion 1 Nano Silica 5 2 Sodium Lauryl Sulfate 4 3 Sodium chloride 2.5
[0061] The raw materials used for the grouting material of this embodiment are shown in Table 8 below.
[0062] Table 8 Grouting material raw material components of Example 4
[0063]
[0064]
[0065] The preparation method of the grouting material of this embodiment comprises the following steps:
[0066] (1) Preparation of modified nano-silica: Sodium dodecyl sulfate was completely dissolved in 50 ml of water, sodium chloride was added, and nano-silica was added after the sodium chloride was completely dissolved, and the mixture was stirred at 55° C. for 15 min, and then poured into a ball mill, and reacted for 30 min using a planetary ball mill at a speed of 300 r / min, and then taken out, washed, centrifuged, and low-temperature dried to obtain modified nano-silica;
[0067] (2) Preparation of carbon nanotube dispersion: Dissolve the polyoxyethylene polyoxypropylene ether dispersant in water, add carbon nanotubes (the ratio of the two is 1:0.8), stir on a magnetic stirrer for 8 minutes, and after the two are dissolved, place the dispersion in an ultrasonic disperser and ultrasonically disperse for 35 minutes to obtain a carbon nanotube dispersion.
[0068] (3) Special cement, fine aggregate, ultrafine mineral admixture and calcium sulfoaluminate expansion agent are mixed and stirred to obtain powder A; modified nano-silicon dioxide and admixtures are mixed and stirred to obtain powder B; powder A and powder B are mixed and stirred, carbon nanotube dispersion and vinyl acetate-ethylene copolymer emulsion are added, and the water-cement ratio is adjusted to 0.166 to obtain high-strength and high-modulus offshore wind power grouting material.
[0069] Example 5
[0070] The raw materials used for the modified nano-silicon dioxide in this embodiment are shown in Table 9 below.
[0071] Table 9 Modified silica raw material components of Example 5
[0072] Serial number raw material Content / portion 1 Nano Silica 6 2 Sodium Lauryl Sulfate 4 3 Aluminum Chloride 3
[0073] The raw materials used for the grouting material of this embodiment are shown in Table 10 below.
[0074] Table 10 Grouting material raw material components of Example 5
[0075]
[0076]
[0077] The preparation method of the grouting material of this embodiment comprises the following steps:
[0078] (1) Preparation of modified nano-silica: Sodium dodecyl sulfate was completely dissolved in 50 ml of water, and aluminum chloride was added. When the aluminum chloride was completely dissolved, nano-silica was added, and the mixture was stirred at 60° C. for 20 min. The mixture was then poured into a ball mill, and reacted for 35 min using a planetary ball mill at a speed of 300 r / min. The mixture was then taken out, washed, centrifuged, and dried at low temperature to obtain modified nano-silica.
[0079] (2) Preparation of carbon nanotube dispersion: Dissolve polyoxyethylene polyoxypropylene ether dispersant in water, add carbon nanotubes (the ratio of the two is 1:0.9), stir on a magnetic stirrer for 9 minutes, and after the two are dissolved, place the dispersion in an ultrasonic disperser and ultrasonically disperse for 40 minutes to obtain a carbon nanotube dispersion.
[0080] (3) Special cement, fine aggregate, ultrafine mineral admixture and calcium sulfoaluminate expansion agent are mixed and stirred to obtain powder A; modified nano-silicon dioxide and admixtures are mixed and stirred to obtain powder B; powder A and powder B are mixed and stirred, carbon nanotube dispersion and vinyl acetate-ethylene copolymer emulsion are added, and the water-cement ratio is adjusted to 0.162 to obtain high-strength and high-modulus offshore wind power grouting material.
[0081] Example 6
[0082] The raw materials used for the modified nano-silicon dioxide in this embodiment are shown in Table 11 below.
[0083] Table 11 Modified silica raw material components of Example 6
[0084] Serial number raw material Content / portion 1 Nano Silica 4 2 Sodium Lauryl Sulfate 4 3 Calcium chloride 3
[0085] The raw materials used for the grouting material of this embodiment are shown in Table 12 below.
[0086] Table 12 Grouting material raw material components of Example 6
[0087] Serial number raw material Content / portion 1 Special cement 40 2 fine aggregate 30 3 Ultrafine mineral admixture 15 4 Calcium sulphoaluminate expansion agent 15 5 Steel Fiber 5 6 Admixtures 2 7 Modified Nano Silica 1 8 Vinyl acetate-ethylene copolymer emulsion 5 9 Carbon Nanotube Dispersion 0.5
[0088] The preparation method of the grouting material of this embodiment comprises the following steps:
[0089] (1) Preparation of modified nano-silica: Sodium dodecyl sulfate was completely dissolved in 50 ml of water, and calcium chloride was added. When the calcium chloride was completely dissolved, nano-silica was added, and the mixture was stirred at 65° C. for 15 min. The mixture was then poured into a ball mill, and reacted for 40 min using a planetary ball mill at a speed of 350 r / min. The mixture was then taken out, washed, centrifuged, and dried at low temperature to obtain modified nano-silica.
[0090] (2) Preparation of carbon nanotube dispersion: Dissolve polyoxyethylene polyoxypropylene ether dispersant in water, add carbon nanotubes (the ratio of the two is 1:1), stir on a magnetic stirrer for 10 minutes, and after the two are dissolved, place the dispersion in an ultrasonic disperser and ultrasonically disperse for 40 minutes to obtain a carbon nanotube dispersion.
[0091] (3) Special cement, fine aggregate, ultrafine mineral admixture and calcium sulfoaluminate expansion agent are mixed and stirred to obtain powder A; modified nano-silicon dioxide and admixtures are mixed and stirred to obtain powder B; powder A and powder B are mixed and stirred, carbon nanotube dispersion and vinyl acetate-ethylene copolymer emulsion are added, and the water-cement ratio is adjusted to 0.16 to obtain high-strength and high-modulus offshore wind power grouting material.
[0092] Comparative Example 1
[0093] The basic steps are the same as those in Example 6, except that no chloride salt is added during the modification of the nano-silicon dioxide. The specific components are shown in Table 13 below.
[0094] Table 13 Modified silica raw material components of comparative example 1
[0095]
[0096]
[0097] Comparative Example 2
[0098] The basic steps are the same as those in Example 6, except that no carbon nanotube dispersion is added. The specific components are shown in Table 14.
[0099] Table 14 Grouting material raw material components of comparative example 2
[0100] Serial number raw material Content / portion 1 Special cement 40 2 fine aggregate 30 3 Ultrafine mineral admixture 15 4 Calcium sulphoaluminate expansion agent 15 5 Steel Fiber 5 6 Admixtures 2 7 Modified Nano Silica 1 8 Vinyl acetate-ethylene copolymer emulsion 5
[0101] Comparative Example 3
[0102] The basic steps are the same as those of Example 6, except that carbon nanotubes are directly used. The specific components are shown in Table 15.
[0103] Table 15 Grouting material raw material components of comparative example 3
[0104]
[0105]
[0106] Comparative Example 4
[0107] The basic steps are the same as those in Example 6, except that no plasticity regulator is added. The specific components are shown in Table 16.
[0108] Table 16 Grouting material raw material components of comparative example 4
[0109] Serial number raw material Content / portion 1 Special cement 40 2 fine aggregate 30 3 Ultrafine mineral admixture 15 4 Calcium sulphoaluminate expansion agent 15 5 Steel Fiber 5 6 Admixtures 2 7 Modified Nano Silica 1 8 Carbon Nanotube Dispersion 0.5
[0110] Performance Testing
[0111] The grouting materials prepared in the above embodiments and comparative examples were subjected to performance testing, and the results obtained are shown in Table 17 below.
[0112] Table 17 Performance results of grouting materials prepared in Examples and Comparative Examples
[0113]
[0114]
[0115] It can be seen from the table that the high-strength and high-elastic offshore wind power grouting material prepared by the present invention has an initial fluidity of ≥320mm, a 30min fluidity of ≥310mm, and good fluidity; 1d compressive strength ≥75MPa, 3d compressive strength ≥125MPa, 28d compressive strength ≥140MPa, has the advantage of ultra-high strength, and 28d elastic modulus ≥54MPa.
[0116] Combining Example 6 and Comparative Example 1, it can be seen that the present invention can introduce chloride salt when modifying nano-silicon, and the fluidity of the entire grouting material is high compared to not introducing chloride salt. Therefore, it can be seen that the addition of chloride salt can effectively prevent the agglomeration of nano-silicon dioxide and improve the dispersibility of nano-silicon dioxide. And further combining Comparative Example 1 and Comparative Example 4, it can be seen that based on the modified nano-silicon dioxide of the present invention, the carbon nanotube dispersion and the vinyl acetate-ethylene copolymer emulsion are combined to further improve the fluidity and strength of the slurry.
Claims
1. A modified nano-silicon dioxide, characterized in that The modified nano-silicon dioxide comprises the following raw materials by weight: 4-8 parts of nano-silicon dioxide, 2-4 parts of anionic surfactant and 2-3 parts of chloride salt; wherein the anionic surfactant is sodium dodecyl sulfate or sodium dodecyl alcohol polyoxyethylene ether sulfate, and the chloride salt is calcium chloride, aluminum chloride or sodium chloride. The modified nano-silicon dioxide comprises the following steps: dissolving the anionic surfactant in water, adding the chloride salt and dissolving it, then adding the nano-silicon dioxide, stirring and reacting at 50-65° C. for 10-20 minutes, then ball milling at a rotation speed of 200-350 r / min for 20-40 minutes, and finally washing, centrifuging and low-temperature drying to obtain the modified nano-silicon dioxide.
2. A high-strength grouting material for offshore wind power, characterized in that The raw materials include the following by weight: 35-40 parts of special cement, 30-35 parts of fine aggregate, 15-20 parts of mineral admixture, 10-15 parts of calcium sulfoaluminate expansion agent, 3-5 parts of steel fiber, 1-2 parts of admixture, 0.5-1 part of modified nano silicon dioxide according to claim 1, 2-5 parts of vinyl acetate-ethylene copolymer emulsion and 0.2-0.5 parts of carbon nanotube dispersion.
3. The offshore wind power high-strength grouting material according to claim 2 is characterized in that: The special cement is a mixture of ordinary Portland cement and sulphoaluminate cement in a weight ratio of 1:(0.1-0.2).
4. The offshore wind power high-strength grouting material according to claim 2, characterized in that: The fine aggregate is a mixture of 10-30 mesh quartz sand and 30-55 mesh quartz sand in a weight ratio of 1:(0.8-1).
5. The offshore wind power high-strength grouting material according to claim 2, characterized in that: The mineral admixture is a mixture of fly ash and mineral powder in a weight ratio of 1:(4-5).
6. The offshore wind power high-strength grouting material according to claim 2, characterized in that: The additives are a polycarboxylic acid water reducer, a defoamer and a plastic expansion agent in a weight ratio of 1: (0.1-0.2): (0.05-0.1), wherein the defoamer is an organosilicon powder defoamer and the plastic expansion agent is azodicarbonamide.
7. The offshore wind power high-strength grouting material according to claim 2, characterized in that: The carbon nanotube dispersion is prepared by the following steps: dissolving a polyoxyethylene polyoxypropylene ether dispersant in water, adding carbon nanotubes and stirring until they are dissolved, and then ultrasonically dispersing for 30-40 minutes to obtain the carbon nanotube dispersion; wherein the mass ratio of carbon nanotubes to dispersant is 1:(0.5-1).
8. A method for preparing the offshore wind power high-strength grouting material according to claim 2, characterized in that The steps include: (1) Special cement, fine aggregate, mineral admixture and calcium sulphoaluminate expansion agent are mixed and stirred to obtain powder A; (2) Mixing and stirring the modified nano-silicon dioxide and the additive to obtain powder B; (3) Powder A and powder B are mixed and stirred, and then added into carbon nanotube dispersion and vinyl acetate-ethylene copolymer emulsion, and the water-cement ratio is adjusted to 0.16-0.17 to prepare offshore wind power grouting material.
Citation Information
Patent Citations
Nano modified self-penetrating water-based repair material and preparation method thereof
CN104628354A
Wind power high-strength grouting material and preparation method thereof
CN114031349A